EVALUATION OF THE INDUSTRIAL PRACTICE PROGRAM USING THE DISCREPANCY EVALUATION MODEL (DEM) IN THE INFORMATICS AND COMPUTER ENGINEERING EDUCATION PROGRAM MAKASSAR STATE UNIVERSITY - Citra Meisarah Asril; M Yusuf Mappeasse; Hasrul Bakri (Sakura Digital Nusantara, 2023)
This research is an evaluation research which aims to evaluate the implementation of industrial practice programs in the Informatics and Computer Engineering Education Study Program, Department of Informatics and Computer Engineering, Faculty of Engineering, Makassar State University using the Discrepancy Evaluation Model (DEM) model which consists of five stages, namely the design/definition stage, implementation stage, process stage, product stage and product comparison stage. The subjects in this research were the Industrial Practice Coordinator and 148 students from the class of 2017 who had carried out industrial practice. The students who were used as respondents were taken using a simple random sampling technique. Data collection was taken through questionnaires, interviews and documentation. Data analysis in this research uses descriptive statistics and is presented in the form of tables and histograms. The research results show that: (1) There is a gap in the implementation of industrial practices in the informatics and computer engineering education study program for students class of 2017 in terms of the design/definition stage with an average total gap value of 0.75, which is in the very insignificant category. (2) There is a gap in the implementation of industrial practices in the informatics and computer engineering education study program for 2017 class students in terms of the implementation stage with an average total gap value of 0.48, which is in the very insignificant category. (3) There is a gap in the implementation of industrial practices in the informatics and computer engineering education study program for 2017 class students in terms of the process stage with an average total gap value of 0.69, which is in the very insignificant category. (4) There is a gap in the implementation of industrial practices in the informatics and computer engineering education study program for the 2017 class of students reviewed as a whole with an average total gap value of 0.65, which is in the very insignificant category.